2022
DOI: 10.3389/fgene.2022.1007519
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic cell cycle defect causes impaired neurogenesis in down syndrome

Abstract: Impaired neurogenesis in Down syndrome (DS) is characterized by reduced neurons, increased glial cells, and delayed cortical lamination. However, the underlying cause for impaired neurogenesis in DS is not clear. Using both human and mouse iPSCs, we demonstrate that DS impaired neurogenesis is due to biphasic cell cycle dysregulation during the generation of neural progenitors from iPSCs named the “neurogenic stage” of neurogenesis. Upon neural induction, DS cells showed reduced proliferation during the early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 107 publications
1
1
0
Order By: Relevance
“…Canonical WNT signaling promotes stem cell proliferation and inhibition of progenitor apoptosis ( Dravid et al, 2005 ; Davidson et al, 2007 ; Lee et al, 2015 ). The decrease in canonical WNT signaling in our results correlates with decreased cell proliferation in T21 ( Sobol et al, 2019 ; Sharma et al, 2022 ). Overall, given the critical role of the canonical WNT signaling pathway in maintaining stemness and proliferation, these data may indicate that T21 cells are less responsive to cues to maintain or expand progenitor pools in the brain.…”
Section: Discussionsupporting
confidence: 61%
“…Canonical WNT signaling promotes stem cell proliferation and inhibition of progenitor apoptosis ( Dravid et al, 2005 ; Davidson et al, 2007 ; Lee et al, 2015 ). The decrease in canonical WNT signaling in our results correlates with decreased cell proliferation in T21 ( Sobol et al, 2019 ; Sharma et al, 2022 ). Overall, given the critical role of the canonical WNT signaling pathway in maintaining stemness and proliferation, these data may indicate that T21 cells are less responsive to cues to maintain or expand progenitor pools in the brain.…”
Section: Discussionsupporting
confidence: 61%
“…This was also confirmed in the Ts65Dn mouse model [ 30 ] and DS-derived organoid models [ 33 , 35 ]. However, other studies found increased numbers of neural progenitors in the SVZ region in the medial ganglionic eminence in Ts65Dn and Ts1Cje mouse models, leading to the enhanced generation of inhibitory neurons accompanied by a paucity in the number of excitatory neurons [ 84 , 85 ]. In addition, impaired neurogenesis was attributed to a biphasic cell cycle defect manifested in the diminished proliferating capacity of NPCs in the early stages, followed by increased proliferation affecting the neurogenic phase of the neurogenesis, as was shown in a DS-derived iPSC-based model [ 84 ].…”
Section: Discussionmentioning
confidence: 99%